3.11 The zooarchaeology of Sand (Scottish Archaeological Internet Reports, 2009)
Excavation at Sand has produced one of the largest Mesolithic faunal assemblages in Britain. Substantial quantities of mammal, bird and fish bones have been analysed. The analysis has revealed a focus on a narrow suite of local resources, including wild terrestrial mammals, seabirds and littoral zone fish. The highly fragmentary nature of the mammal assemblage makes interpretation difficult. If the fragmentation is not the result of post-depositional processes, tentative suggestions are the possible skinning of red deer and wild boar, the extraction of bone fat and tool manufacture. The bird remains are dominated almost exclusively by razorbills and guillemots, and their behavioural and breeding patterns place the time of their capture in late spring and early summer, or late summer and autumn. The fish assemblage is dominated by fish from the cod family and wrasse family. The total length estimate distributions for the main gadid taxa, saithe and Pollack, point towards one or more seasons of fishing, targeting different sizes of fish. If this does represent two seasons of fishing, late summer and autumn (possibly into winter), and late spring are the most likely. Based on the size and species of fish, it is likely that stationary traps and nets were the primary method of fishing at Sand.